Evaluation of Transient Ischemic Dilation (TID) Ratio in Gated SPECT Myocardial Perfusion Imaging (MPI) with Pharmacological Stress Agents (Bangladesh Journal of Nuclear Medicine, 2019)
Objectives: Transient ischemic dilation (TID) refers to an apparent increase in the size of the left ventricular cavity on stress myocardial perfusion imaging compared to rest imaging. This study was performed to correlate the value of TID ratio in gated SPECT MPI in Coronary Artery Disease (CAD).Patients & Methods: Seventy-four suspected or known CAD patients underwent MPI performed with Tc-99m sestamibi. Single day stress - rest protocol with pharmacological stress was followed, according to established practicing protocol of NINMAS. A statistical analysis was carried out by using the Statistical Package for Social Sciences version 20.0 for Windows (SPSS Inc., Chicago, Illinois, USA). Student t-test was used for continuous variables. Chi-square test used to compare categorical data. P values